The chimera-type galectin-3 is a positive modulator of trophoblast functions with dysregulated expression in gestational diabetes mellitus - Freitag, Nancy (2020)
Problem: From conception, a delicate regulation of galectins, a family of carbohydrate-binding proteins, is established to ensure maternal immune tolerance in pregnancy. Though galectin-3 (gal-3), the only chimera-type galectin, is abundantly expressed at the feto-maternal interface; the physiological role of this lectin during pregnancy remains to be fully elucidated and requires further investigation. Method of study: In this study, we analyzed serum gal-3 levels during the course of healthy gestation. Trophoblast functions were evaluated upon gal-3 exogenous stimulation using trophoblastic cell lines (e.g, HIPEC65, SGHPL-4, and BeWo cells). Finally, we investigated variations in peripheral gal-3 levels associated with the development of spontaneous abortion and gestational diabetes mellitus (GDM). Results: Gal-3 circulating levels increased as normal pregnancy progressed. In vitro experiments showed that exogenous gal-3 positively regulated trophoblast functions inducing invasion, tube formation, and fusion. Compared with normal pregnant women, circulating gal-3 levels were significantly decreased in patients who developed GDM. Conclusion: Our results reveal a physiological role for gal-3 during pregnancy, promoting proper trophoblast functions associated with healthy gestation. GDM is associated with a failure to increase circulating gal-3 levels late in gestation. Thus, dysregulation of gal-3 may indicate a contribution of the chimera-type lectin to this adverse pregnancy outcome.